Hebitren dan Pemberdayaan Ekonomi Pesantren di Soloraya - Aji Saputro; Putri Ayu Kusuma Wardani; Kharisma Desrianis Ramadani (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2022)
The development of pesantren (Islamic boarding school) into opportunities as an economic improvement through empowerment is one of the efforts to be independent by joining HEBITREN. Apart from being a place to study about religion, pesantren has also be able to provide welfare and be independent in management. This study aims to determine the empowerment of pesantren through hebitren of Solo Raya in improving the economy. As the development of the era, the opportunity of pesantren in economy are also increased. The method used in this study is qualitative with a descriptive approach. The data of the study was collected through interviews and observations. The results show that the program carried out by hebitren in Solo Raya increased the efforts in improving the economy of pesantren in Solo Raya.